Schoolchildren’s opinions regarding the incidence of violence at school - Błońska, Barbara; Gotlib, Joanna (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Aggression and violence among adolescents are now common. The most important underlying causes are low self-esteem, lack of authorities and family ties, and the failure of an adolescent to cope with his/her problems. Aim of the study. This study aimed to investigate the extent of violence at school and gather school-goers’ opinions regarding violence. Material and methods. An anonymous questionnaire designed by the authors was distributed among 100 junior secondary school students in Warsaw in March 2009. Results. The vast majority of the respondents (71%) declared that they feel safe at school, 73% have witnessed violence in the school, and 29% reported being a victim of violence. Three out of four respondents have encountered physical violence, 73% declared that acts of violence were usually perpetrated by older students. The respondents have also encountered violence from their peers and teachers. Conclusions: 1. In the light of these results and literature data, it appears that existing programmes and actions to prevent violence at school are ineffective. 2. It appears advisable to continue this research in a group of teachers in order to identify teachers’ needs regarding forms and methods of preventing violence among learners.